Mitophagy: A New Player in Stem Cell Biology - Cairns, George (Biology (Basel), 2020)
SIMPLE SUMMARY: Stem cells are required to create all organs and tissues during development, as well as replace or regenerate tissues in adulthood. Stem cells are characterized by two main factors, which are (1) the ability to replenish themselves in order to maintain their population for further use, and (2) the ability to differentiate into specialized cells. These two characteristics are regulated by both external and internal factors. One of these internal factors is mitochondrial function. Mitochondria are organelles that serve an essential role to cells by providing energy and regulating cell survival. These organelles are now known to be important for allowing the stem cell characteristics. Given that proper mitochondrial function is crucial for cells, when they become defective they need to be removed. This process of removal, known as mitophagy or “mitochondrial eating”, is emerging as an important player in stem cells. In this review we discuss the new research that shows the importance of mitophagy in having functional stem cells. ABSTRACT: The fundamental importance of functional mitochondria in the survival of most eukaryotic cells, through regulation of bioenergetics, cell death, calcium dynamics and reactive oxygen species (ROS) generation, is undisputed. However, with new avenues of research in stem cell biology these organelles have now emerged as signaling entities, actively involved in many aspects of stem cell functions, including self-renewal, commitment and differentiation. With this recent knowledge, it becomes evident that regulatory pathways that would ensure the maintenance of mitochondria with state-specific characteristics and the selective removal of organelles with sub-optimal functions must play a pivotal role in stem cells. As such, mitophagy, as an essential mitochondrial quality control mechanism, is beginning to gain appreciation within the stem cell field. Here we review and discuss recent advances in our knowledge pertaining to the roles of mitophagy in stem cell functions and the potential contributions of this specific quality control process on to the progression of aging and diseases.